A Study of the Impact of Wind load on Low-rise building by Different window to wall ratios by Computational Fluid Dynamics: Case study of Warehouse building - ภาวรัศมิ์ ณราพัช; ทักขนนท์ ภัทรนันท์; สุริต ศิรเดช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research presents a study on the relationship between the window-to-wall ratio (WWR) and wind forces acting on structures, focusing on warehouse buildings in Thailand. These buildings frequently experience wind-induced damage, leading to structural failures and envelope deterioration. The study CFD simulations using Autodesk CFD to analyze the effects of wind loads on buildings with varying window openings and wind directions. The simulations are based on 3D RANS equations, utilizing the Standard k-ε Turbulent model. 4 WWR (0.20, 0.30, 0.40, 0.50) and 3 wind directions (across wind, along wind, and oblique wind) by Simulation-based research to study the effects of average wind pressure and summary force to compare the resultant force (FR) acting on a warehouse building, these found in the case of equal openings WWR 0.20, perpendicular wind exposure generates the highest resultant force on the windward wall. Additionally, significant variations in wind-induced forces are observed between the windward & leeward walls WWR 0.20&0.30, WWR 0.20&0.40 and WWR 0.20&0.50, respectively. These findings demonstrate the interaction between differences in WWR on the windward and leeward sides and the forces acting on the structure